Spectroscopic Tools Applied to Flerovium Decay Chains. (December 2020) - Cox, D. M.; Såmark-Roth, A.; Rudolph, D.; Sarmiento, L.G.; Fahlander, C.; Forsberg, U.; Golubev, P.; Heery, J.A.M.; Yakushev, A.; Albers, H. M.; Block, M.; Brand, H.; et al.
Abstract: An upgraded TASISpec setup, with the addition of a veto DSSD and the new Compex detector-germanium array, has been employed with the gas-filled recoil separator TASCA at the GSI Helmholtzzentrum für Schwerionenforschung Darmstadt, to study flerovium (element 114) decay chains. The detector upgrades along with development of new analytical techniques have improved the sensitivity of the TASISpec setup for measuring α -photon coincidences. These improvements have been assessed with test reactions. The reaction 48 Ca+ 206, 207 Pb was used for verification of experimental parameters such as transmission to implantation DSSD and target-segment to α -decay correlations. The reaction 48 Ca+ nat Hf was used to produce several short-lived nuclei with multiple-α decay chains to investigate pile-up event deconvolution.